CRIMINAL RESPONSIBILITY OF BUSINESS ENTITY LEADERS FOR DEDUCTIONS OF PARTICIPANTS OF EMPLOYMENT SOCIAL SECURITY ORGANIZING AGENCY IN PEKANBARU CITY - Silaen, Gabriel Francius; Afrita, Indra; Harahap, Irawan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
ABSTRACTArticle 55 of Law Number 24 of 2011 concerning the Social Security Administering Body regulates criminal sanctions in imprisonment and fines for business entities that do not pay and deposit their workers' BPJS employment membership contributions to the local BPJS employment. The purpose of the study is to analyze criminal liability; and to examine obstacles and efforts to overcome them. The research method is sociological legal research, legislative approach, and cases; the research location is the Pekanbaru BPJS Employment Branch Office; population and samples from relevant sources; data sources are primary, secondary, and tertiary; data collection techniques are observation, structured interviews, and document/literature studies; data analysis is qualitative with conclusions: inductive. The study results are that Article 55 of Law Number 24 of 2011 concerning BPJS has not been fully implemented, because of the 25 business entities in Pekanbaru City that have not paid and deposited membership contributions, only 2 business entities have been subject to criminal sanctions. The implementation of criminal sanctions against the leaders of the business entity has encountered obstacles. The obstacles and efforts to overcome the obstacles are legal factors/legislation, namely: Legal factors/legislation, namely the lack of regulations governing expert witnesses so that evidence is difficult, the police's efforts to allocate a budget to present expert witnesses; Criminal law enforcement procedures in regulations must go through long and multi-sector stages, efforts to improve coordination and cooperation between agencies. Law enforcement/government factors, namely the lack of coordination and cooperation between agencies for settlement through litigation, these agencies by improving coordination and cooperation to take the litigation route; police investigators' knowledge is still limited, investigators are taking Vocational Education; ultimatum remidium is prioritized by the police, efforts if it has been 2 times then the police must apply criminal penalties; The commitment to law enforcement that has not been fully implemented by the Riau Regional Police, efforts to enforce the law according to the law; Lack of socialization so that companies are not aware of the existence of criminal sanctions, efforts to increase the intensity of the approach in terms of coaching and supervision. Community factors, namely differences in worker positions make workers afraid to report their superiors, efforts are made so that workers have the courage to report; Low worker awareness to protect themselves from the risk of work accidents, efforts are made to organize education and training; uncooperative business entities and workers have complicated the handling process at the Riau Province Manpower and Transmigration Service, efforts are made to provide guidance by the agency to business entities. Keywords: Criminal Liability, BPJS Contributions, Pekanbaru ABSTRAKPasal 55 Undang-Undang Nomor 24 Tahun 2011 tentang Badan Penyelenggara Jaminan Sosial mengatur sanksi pidana penjara dan denda bagi badan usaha yang tidak membayar dan menyetorkan iuran kepesertaan BPJS kerenagakerjaan pekerjanya kepada BPJS kerenagakerjaan setempat. Tujuan penelitian ialah Untuk menganalisispertanggungjawaban pidananya; Untuk menganalisis hambatan dan upaya mengatasinya. Metode penelitiaan yaitu penelitian hukum sosiologis, pendekatan perundang–undangan dan kasus; lokasi penelitian yaitu Kantor Cabang BPJS Ketenagakerjaan Pekanbaru; populasi dan sampel dari narasumber–narasumber relevan; sumber data ialah primer, sekunder dan tersier; teknik pengumpulan data ialah observasi, wawancara terstruktur dan studi dokumen/kepustakaan; analisis datanya kualitatif dengan kesimpulan: induktif. Hasil penelitian yaitu belum terlaksana sepenuhnya dalam Pasal 55 Undang-Undang Nomor 24 Tahun 2011 tentang BPJS , dikarenakan dari 25 badan usaha di Kota Pekanbaru yang belum membayar dan menyetor iuran kepesertaan baru 2 badan usaha yang diterapkan sanksi pidananya. Penerapan sanksi pidana terhadap pimpinan badan usaha tersbeut mengalami hambatan. Hambatan dan upaya mengatasi hambatannya adalah Faktor hukum/peraturan perundang-undangan, yaitu: Faktor Hukum/peraturan perundang-undangan yaitu masih kurang regulasi yang mengatur saksi ahli sehingga sulitnya pembuktian, upayanya pihak Kepolisian mengalokasikan anggaran guna menghadirkan saksi ahli; Prosedur penegakan hukum pidana dalam regulasi harus melalui tahapan panjang dan multi sektor, upayanya meningkatkan koordinasi dan kerjasama antar instansi. Faktor aparat penegak hukum/pemerintah yaitu Kurangnya koordinasi dan kerjasama antar instansi untuk penyelesaian secara litigasi, para instansi tersebut dengan meningkatkan koordinasi dan kerjasama untuk menempuh jalur litigasi; pengetahuan penyidik kepolisian masih terbatas, penyidiknya mengikuti Pendidikan Kejuruan; ultimum remidium dikedepankan kepolisian, upayanya jika sudah 2 kali maka pihak kepolisian harus menerapkan pemidanaan; Komitmen penegakan hukum yang belum sepenuhnya oleh Kepolisian Daerah Riau, upayanya melaksanakan penegakan hukum sesuai undang-undang; Kurangnya sosialiasai sehingga perusahaan tidak mengetahui adanya sanksi pidana, upayanya meningkatkan intensitas pendekatan dalam hal pembinaan dan pengawasan. Faktor masyarakat yaitu perbedaan posisi pekerja membuat pekerja takut melaporkan pimpinannya, upayanya Agar pekerja mempunyai keberanian melaporkan; Rendahnya kesadaran pekerja untuk memproteksi diri dari resiko kecelakaan kerja, upayanya menyelenggarakan pendidikan dan pelatihan; badan usaha dan pekerjanya yang tidak kooperatif telah mempersulit proses penangannnya di Dinas Ketenagakerjaan dan Transmigrasi Provinsi Riau, upayanya dilakukan pembinaan oleh Dinas instansi tersebut terhadap badan usaha.Kata Kunci: Pertanggungjawaban Pidana, Iuran BPJS, Pekanbaru